Analisis Hukum Terhadap Klausula Eksonerasi pada Nota Laundry di Kecamatan Padang Hilir, Kota Tebing Tinggi Perspektif Wahbah Az-Zuhaili - Siregar, Wilma Putri Handayani; Permata, Cahaya (Fakultas Syariah INSURI Ponorogo, 2023)
Business actors in Padang Hilir Subdistrict, Tebing Tinggi City make exoneration clauses to release responsibility for damage and loss experienced by consumers. The consumer protection law stipulates that business actors may not include exoneration clauses in offering goods and/or services intended for trade. The purpose of this study is to find out what the factors causing the use of exoneration clauses in laundry notes, how the regulation of exoneration clauses according to legislation, and how the responsibility for using exoneration clauses by business actors in Padang Hilir District, Tebing Tinggi City from the perspective of Wahbah Az-Zuhaili. This type of research is empirical juridical with a living case studies approach, statute approach, and conceptual approach. The results showed that the liability of business actors using an exoneration clause on laundry notes is inappropriate, while according to Wahbah Az-Zuhaili business actors must be responsible for damage and loss experienced by consumers. In conclusion, the exoneration clause based on Wahbah Az-Zuhaili's opinion cannot be used to release responsibility. If anyone makes such a clause, it is null and void